Soil and Air Temperature Calibrations Using Branched GDGTs for the Tropical Andes of Colombia: Toward a Pan‐Tropical Calibration - Lina C. Pérez‐Angel; Julio Sepúlveda; Peter Molnar; Camilo Montes; Balaji Rajagopalan; Kathryn Snell; Catalina Gonzalez‐Arango; Nadia Dildar (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial cell membrane lipids that, when preserved in sedimentary archives, can be used to infer continental paleotemperatures. Although commonly used global calibrations capture a relationship between the distribution of brGDGTs and temperature, they underestimate temperatures for tropical regions as much as ~16°C. Furthermore, some global calibrations reach saturation at around 24–25°C, and, in general, they have root‐mean‐squared errors (RMSEs ≈ ~4°C) that are too large for them to resolve small variations in paleoclimate variability in tropical regions. We present an in situ regional calibration of soil brGDGTs along altitudinal transects on both flanks of the Eastern Cordillera of Colombia in the northern tropical Andes that spans ~3,200 m in elevation and 17°C and 19°C in mean annual soil and air temperatures, respectively. These new soil and air regional calibrations yield RMSEs of 1.5°C and 1.9°C, respectively. When combined with existing data from elsewhere in the tropics, the integrated data (n = 175) not only fit a linear calibration with a RMSE of 2.7°C but also fit a nonlinear calibration with a RMSE of 2.2°C. These calibrations allow for a more precise and reliable reconstruction of past temperatures in the tropics than global calibrations.